The Bundesverfassungsgericht$1 (Bs human dignity review: Solange III and its application in subsequent case laws - Clara Rauchegger (Edward Elgar Publishing, 2018)
In its Solange III judgment, the Bundesverfassungsgericht, the German Federal Constitutional Court, attached a new condition to the primacy of EU law over German constitutional law. It turned the constitutional identity review that it had introduced in its Lisbon judgment into a safeguard mechanism for the protection of human dignity in individual cases. The chapter examines the advent of this new condition in Solange III and its application in subsequent case law of the Bundesverfassungsgericht.
English
Keywords: German law; Fundamental Rights Agency; Fundamental Rights; Solange III; Courts